Weeds of the Lesser Antilles - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Weeds of the Lesser Antilles (Mauvaises herbes des Petites Antilles) INRA - 147 rue de l'Universite 75007 Paris - FRANCE